Surfactant flow between a Plateau border and a film during foam fractionation - Grassia, Paul (2016)
A fluid mechanics problem relevant to foam fractionation processes is analysed. Specifically the fluid flow field transporting surfactant from foam Plateau borders (fed with surfactant-rich material) towards comparatively surfactant-lean foam films is considered. The extent to which this surfactant mass transfer is limited by surface viscous effects is studied. Previous work (Vitasari et al., 2016) made assumptions about the likely flow field along the Plateau border surface. These assumptions suggested that ?high? surface viscosity (measured by a suitable dimensionless parameter) led to strong suppression of the rate of surfactant mass transfer from Plateau border to film, whereas ?low? surface viscosity did not suppress this mass transfer rate in any significant way. More detailed fluid mechanical calculations which are carried out here corroborate the aforementioned assumptions in the ?high? surface viscosity regime. However the calculations suggest that in the ?low? surface viscosity regime, in contrast to the findings from the previous assumptions, moderate reductions in the rate of surfactant mass transfer are also possible. Counterintuitively these moderate reductions in mass transfer rate potentially have more negative impact on fractionation processes than the aforementioned strong suppression. This is because they tend to arise under conditions for which the efficiency of the fractionation system is particularly sensitive to any reduction whatsoever in the surfactant mass transfer rate.